Should we customise critical value procedure according to patient origin and laboratory turnaround time?. Issue 4 (31st January 2013) - Salinas, Maria; López-Garrigós, Maite; Gutiérrez, Mercedes; Lugo, Javier; Flors, Lucia; Leiva-Salinas, Carlos
Abstract : Introduction: Our routine laboratory critical value notification procedure is based on a short list of six fundamental critical values. The report system for our Stat laboratory is not based on this 'short list'; instead, critical values are always reported according to the patient clinical context and the previous laboratory results. The aim of our work is to show how a critical value notification procedure based on a rigid list of values and thresholds can result in completely different results depending on whether the tests are requested in a stat or a routine manner. Material and methods: We reviewed the number of critical value notifications based on the short list for the routine laboratory. For the stat laboratory, we studied the number of real notifications based on the pathologist validation of the individualised situation of the patient and calculated the number of notifications that would have been reported if the routine short list would have been used instead. Results: The number of critical values that would have been reported if using the routine short list in stat laboratory was high when compared with the number of critical values that were really reported. Conclusions: Using a rigid list of laboratory values to notify critical values resulted in completely different results depending on whether the tests were requested in stat or routine. Reporting only really unexpected values through an individual custom-made reporting procedure may avoid the wasting of time and resources and raising false alarms among referring physicians and patients.